Correlation between blood variables of the protein profile and beta-hydroxybutyrate ewe lambs - Ortunho, Vanessa Veronese; Maral, WilmarSachetin; Peres Carvalho, Gabriela Souza [UNESP]; Souza Carli, Maria Eduardade; Beline, Mariane [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
The objective of this study was research the correlations between the proteic profile and beta-hydroxybutyrate. The objects of the study were 30 Suffolk ewes randomly distributed in two groups of 15 females. A control group received inorganic commercial mineral salt and the challenge group received commercial mineral salt containing some organic minerals in the carboaminofosfoquelate form. Mineral salt consumption started when the females were approximately 4 months old. The adopted system was confinement and feeding consisted of commercial ration (23.04% PB), sugar cane, water and mineral salt, supplied ad libitum. Reproduction started when the females were approximately 8 months old. All animals had blood collected monthly, who started in reproduction and finished 10 days after parturition. The correlations studied showed different behaviors according to the parameters analyzed.
Keywords: Blood; Minerals; Sheep